Program Pembiasaan Sholat Berjamaah dalam Membentuk Karakter Santri di Asrama Putri Al-Husna Pondok Pesantren Al-Hikamussalafiyah Cipulus - Halimah, Ade; Ahmadiah, Didih; Maulana, Arif; Supendi, Dede (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2023)
This research was conducted because of problems regarding character that were found in the field, where there were complaints submitted by parents. This Islamic boarding school is an educational institution that is the choice in instilling character education. The purpose of this study is to find out how the habituation of congregational prayers is carried out in shaping the character of the santri, especially religious and disciplinary characters. The method used is to use qualitative methods with a case study approach, with data collection techniques by interviews, observation and documentation. The results of the research that has been carried out are the habituation of congregational prayers at the Al-Husna Girls Dormitory carried out every day, especially at dawn, sunset and evening prayers. This habituation can form the religious and disciplined character of the students which can be seen from their activities, where the students are used to and are consistent in attending congregational prayers in a timely manner. And the supporting factors are adequate facilities and infrastructure, the role of administrators, and the awareness of the students who have formed, while the inhibiting factors are the use of the hall for other activities and the feeling of laziness that exists within the students. And the efforts made to overcome the obstacles that occur are by fulfilling facilities and infrastructure, minimizing the use of halls, cooperation between administrators and imposing sanctions.